2012
DOI: 10.1007/s11064-012-0816-z
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Properties and Inflammatory Potential of Citrullinated Myelin Basic Protein Peptide 45–89

Abstract: Deimination of arginyl residue of myelin basic protein (MBP) reduces cationicity of MBP and impedes the normal myelin membrane assembly. Less ordered structure of MBP is more susceptible to proteolytic attack that may lead to the release of highly immunogenic deiminated peptides into extracellular milieu. We have studied the association of peptides 45-89 derived from citrullinated MBP (C8 isomer) and phosphorylated MBP (C3 isomer) with the myelin lipids in a model membrane system using optical waveguide lightm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…39 Myelin basic protein is important for maintaining the structural stability of myelin and is an essential component for efficient nerve conduction. 43 Prior regular exercise has been shown to have a positive impact on reducing demyelination and axonal damage in the spinal cord of EAE animals, as well as on dendritic damage in striatal neurons. 44 A decrease in MBP expression reflects the demyelinating status of MS. 45 The present study showed a decrease in MBP levels in the Cup group, and, conversely, improved MBP expression in Cup+MP and Cn+Cup+HIE gropus.…”
Section: Discussionmentioning
confidence: 99%
“…39 Myelin basic protein is important for maintaining the structural stability of myelin and is an essential component for efficient nerve conduction. 43 Prior regular exercise has been shown to have a positive impact on reducing demyelination and axonal damage in the spinal cord of EAE animals, as well as on dendritic damage in striatal neurons. 44 A decrease in MBP expression reflects the demyelinating status of MS. 45 The present study showed a decrease in MBP levels in the Cup group, and, conversely, improved MBP expression in Cup+MP and Cn+Cup+HIE gropus.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant citrullination has been detected in myelin proteins (ie, MBP), 148 and is proposed to contribute to myelin sheath instability and increased proteolysis with release of immunogenic peptides, 149,150 eventually leading to oligodendrocyte apoptosis. 151 …”
Section: Epigenetics In Multiple Sclerosismentioning
confidence: 99%
“…Nitrite accumulation was used as an index of NO production and inflammatory activation in general. The assay was carried out as in our previous works ( Shanshiashvili et al, 2012 ). The widely used bacterial antigen LPS (a proinflammatory agent) was used to evaluate the inflammation rate in cultured astrocytes.…”
Section: Methodsmentioning
confidence: 99%